Parameters of effective competition activity and selection of young gymnasts in age 9-10 years - A.A. Bolyak; A.A. Pomazan (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to determine the effective factors of competitive activities and criteria for selection of young gymnasts at the stage of preliminary basic training based on the tests of motor skills and physiological parameters using methods of statistical analysis. Material : results of psychophysical testing, anthropometry, data on the development of motor abilities of young gymnasts of 9-10 years and assessment of their technical training. The study group consisted of 29 young gymnasts aged 9-10 years. All of them had a sports category corresponding their ages. Results: among the sixteen benchmarks psychophysiological data figures stepwise regression equation determined the four most important factors that influence the effectiveness of the competitive activities of the young athletes. The stepwise regression equation allowed lowing the most influential factor affecting the competitive activity among anthropometric and motor performance from twenty- eight to twelve most significant factors. Conclusions: The application of regression analysis and stepwise regression method allowed developing the mathematical models of the efficiency of competitive activities of the gymnasts of 9-10 years that can be used in the practice of selection children for the pre basic training.